Thermal Performance and Emission Characteristics of Vented Charcoal Stove - O. S. Olaoye; A. A. Adegbola; O. R. Oyetunji (Archives of Current Research International, 2018)
An improved charcoal stove was designed, constructed and tested in this study to evaluate the thermal performance and combustion efficiency. The evaluation was done in order to know its performance when compared with the commonly found charcoal stove in the locality. Boiling water and rice cooking tests were carried out using the two types of stoves. The time taken, fuel consumption, CO and CO2 emission were measured during the test in the kitchen. The values of time taking, fuel consumption, CO and CO2 for improved and local are 86.95 min/kg, 93.17 min/kg; 0.104, 0.093; 11 PPM, 180 PPM; and 478 PPM, 1271 PPM respectively. A better performance was obtained for the improved coal stove in terms of specific fuel consumption and cooking duration. The burning rate for improved coal stove is 0.0129 kg/min and this shows economic and efficient fuel consumption than the other stove that is 0.0155 kg/min. The thermal efficiency of the improved stove is 17.61% while that of the local stove is 16.41%. Also, improved charcoal stove shows better combustion efficiency of 2.3% as against 14.16% for the local stove. There is CO reduction to an acceptable limit of EPA for improved stove while cooking.